A systematic scoping review of mentor training in medical education between 2000 and 2024 - Jun Rey Leong; Adele Yi Dawn Lim; Nila Ravindran; Darius Wei Jun Wan; Varsha Rajalingam; Jun Kiat Lua; Hannah Yi Fang Kwok; Krish Sheri; Victoria Jia En Fam; Ranitha Govindasamy; Nur Amira Binte Abdul Hamid; Michael Dunn; et al. (BMC Medical Education)
Abstract Background Effective mentoring in medical education facilitates professional development amongst mentees and mentors, improves patient care and outcomes, as well as advances the reputation of the host organisation. Much of this success is guided, assessed and overseen by the mentor. Yet, mentor training remains inconsistent, poorly supported and often inadequately evaluated. Acknowledging mentor training as an essential aspect of mentoring programs, we propose a review to map current features and approaches to mentor training with the hopes of boosting the effective design of a proposed mentoring program. Methods PubMed, Scopus, Embase, PsycINFO and CINAHL database searches were conducted for articles published between 1st January 2000 and 31st March 2024 on mentor training programs in medical education. This systematic scoping review was directed by a PRISMA-guided Systematic Evidence Based Approach (SSR in SEBA). Results A total of 1124 abstracts were reviewed, 63 full-text articles were appraised and 69 articles were included. Five key domains were identified: 1) mentor qualities, 2) training structure, 3) content, 4) outcomes, and 5) obstacles. Conclusion This SSR in SEBA reiterates the critical role of mentor training and introduces evidence of its impact on the professional identity formation (PIF) of prospective mentors. It also highlights that more programs are employing longitudinal mentoring processes to guide the inculcation of desired mentoring characteristics amongst prospective mentors. These efforts to nurture the PIF of the prospective mentor—to better shape their future mentee’s PIF—is novel and requires careful study.